Emotional intelligence, power dynamics, and long-term orientation in exporter-importer relationships: The moderating role of interdependence and incompatibility - Leonidou, Leonidas C.; Aykol, Bilge; Christodoulides, Paul (My University, 2022)
Drawing on Emotion Regulation Theory, we propose a model conceptualization the role of emotional intelligence in achieving long-term orientation in exporter-importer relationships, through the proper exercise of power sources. The model was empirically tested with structural equation modeling using data collected from 262 Greek export manufacturers. The results reveal that the exporter’s emotional intelligence is positively related to the exercise of non-coercive power, but negatively associated with the use of coercive power on the importer buyer. As opposed to coercive power, noncoercive power was conducive to increase communication and decreases conflict between interacting parties. In turn, high levels of communication and low levels of conflict were found to enhance long-term orientation in the exporter-importer relationship. Finally, high levels of interdependence and incompatibility between the two parties are responsible for enhancing the positive effect of non-coercive power on communication and further reducing its negative impact on conflict, while the reverse was true with regard to the use of coercive power.
Keywords: Emotional intelligence; Power sources; Long-term orientation; Exporter-importer relationships